Genetic Algorithm based Secure Hybrid Routing Technique for IoT Framework - Kumar , Rakesh (SOTVI, 2024)
Internet is gaining new heights in today’s technological environment. Internet of things (IoT) is a new class of Internet-basedheterogeneous networked application systems that uses various types of sensors/detectors and devices for the exchange and collection of data. Due to their applications in situations such as building home automation, emergencies, crisis management, energy management, and healthcare, path optimization and message security becomes of topmost importance in IoT. An optimized routing scheme using intelligent mathematical techniques including Genetic Algorithms (GA) and Analytical Hierarchy Process (AHP), is proposed here and an optimized route can be encrypted using cryptographic techniques. From the simulation results, it has been found that the overall efficiency of the IoT system can be greatly improved with the proposed model. A comparison is also provided in the discussion section which demonstrates that hybrid algorithms developed for IoT systems perform much better than traditional routing algorithms.